Romantic Remixers: Hidden Tropes of Romantic Authorship in Creators’ Attitudes about Reuse - Pappalardo Kylie; Aufderheide Patricia (Cultural Science)
This article draws from data generated in existing studies in Australia and the U.S. to examine how creators describe themselves and their creative acts when they are recombining or trying to combine copyrighted work with their own work. It finds a surprising congruence of self-perception across very different copyright regimes and creative practices. An undercurrent of Romantic notions about the originality of creative genius runs through even cutting-edge digital practices. This attitude then bolsters strategies used by large media interests to expand copyright monopoly rights and extend them internationally. Results have implications both for policy and advocacy, in particular, how creators respond to campaigns for expanded copyright exceptions, and a reluctance by even remix creators to challenge the legal structures that restrict their creative practice.